GROWTH STIMULATING ACTIVITY OF NEW PLANT GROWTH REGULATORS (Experimental biology, 2021)
This study was conducted to evaluate growth stimulating activity of new biologically active compounds on shoot germination and seedlings length of wheat and spruce seeds. The best results were obtained by the treatment of spruce seeds with the preparations 3 and 5, where spruce seeds germination was 87.7 − 88%, whereas for the control it was 84%, for the standard − 86 %, and seedlings length in these experiment options was from 8.5 cm to 8.8 cm, for the control − 4.0 cm, for the standard − 7.2 cm. Germination energy and formed shoots germination on wheat seeds were for the control 64.5% and 83.5%, respectively, for KN-2 preparation at 0.01% concentration were 71.0% and 85.5%, for the compound 6 at the concentration 0.1% − 98.0% and 98.5%, at 0.01% concentration − 82.5% and 84.4 %. Using of the growth stimulant 6 completely suppresses the development of saprophytic and pathogenic microflora. The stimulant 7 showed at 0.01% concentration a high shoot forming activity by Spirea propagation, where averaged shoot length was 3.91 cm compared to the control, Cornevin, KN-2 (1.63; 2.58; 3.59 cm, respectively ) and the average percentage of rooted propagules was 44%, similar to the standards (Cornevin and KN-2). The growth stimulant 10 was the most effective and showed a high root forming activity at 0.01% concentration by propagation processing, where the averaged root length was 3.4 cm as compared to the control, Cornevin, KN-2 (1.63, 2.26, 1.67 cm, respectively). A high percentage of rooting at 0.001% concentration was 63%, which exceeds the control and standards Cornevin and KN-2 by 43%, 53%, 52%, respectively. Obtained results of the research demonstrate that the treatment of seedlings with the growth stimulants activates the formation of the root system and shoots.